Pengaruh Stres Dan Lingkungan Kerja Terhadap Kinerja Yang Dimediasi Motivasi Kerja Karyawan Hotel MM UGMYogyakarta - Rahmat Abdullah (Journal of Tourism and Economic, 2020)
This research was conducted at MMUGM Hotel Yogyakarta, aimed to analyze and explain the effect of job Stress and Work Environment on Employee Performance with motivation as mediate variable. This study uses quantitative descriptive method, data collected through questionnaires and interviews, population of 85 people also used as sample known as census sampling methode, data was tested and analyzed using multiple linear regression and path analysis. The result of data analyze shows that the work environment has a positive and significant effect on employee's motivation and performance, job stress does not have positive and significant effect to employee's motivation and performance, work motivation mediates the effect of work stress on employee performance and motivation does not mediate the effect of work environment on employee performance MMUGM Hotel Yogyakarta.